Combination Treatment With Paclitaxel, Carboplatin, and Cetuximab (PCE) as First-Line Treatment in Patients With Recurrent and/or Metastatic Nasopharyngeal Carcinoma - Ueda, Yuri; Enokida, Tomohiro; Okano, Susumu; Fujisawa, Takao; Ito, Kazue; Tahara, Makoto (Frontiers in Oncology, 2020)
Background: Platinum-containing doublet chemotherapy regimens are generally considered the standard first-line systemic therapy for recurrent or metastatic (R/M) nasopharyngeal cancer (NPC). Gemcitabine (GEM) plus cisplatin (CDDP) has become a standard therapy based on a phase 3 study in several countries, yet this regimen sometimes affects quality of life due to nausea or appetite loss. Here, we present the manageable toxicity and promising activity of paclitaxel + carboplatin + cetuximab (PCE) therapy for R/M NPC. Materials and Methods: We conducted a retrospective review of patients with R/M NPC who were treated with PCE from 2013 to 2019 at the National Cancer Center East, Kashiwa, Japan. PCE consisted of PTX 100 mg/m2 on days 1 and 8; CBDCA area under the blood concentration-time curve (AUC) 2.5 on days 1 and 8, repeated every three weeks; and cetuximab at an initial dose of 400 mg/m2, followed by 250 mg/m2 weekly, as reported in the paper. Results: Fourteen patients were identified, consisting of 10 males and 4 females with a median age 59.6 years (range, 43-74). Among the 12 of 14 patients assessed for efficacy, overall response rate was 58.3%, with 2 complete responses and 5 partial responses. On median follow-up of 23.8 months, median overall survival was not reached with observed death events of 2. Median PFS was 4.1 months (95% CI, 2.6-5.6 months). Two patients experienced disease progression during cetuximab maintenance and restarted PCE treatment, then achieved partial response again. The most common grade 3 or 4 adverse events were neutropenia (21.4%) and skin reaction (14.3%). No treatment-related death was observed. Conclusion: Although the number of study population was small, our results suggest that PCE is feasible and potentially effective for R/M NPC, with a 58.3% response rate and 4.1-month PFS. Further prospective evaluation is warranted.